Phylogeographic variation of the Karoo bush rat, Otomys unisulcatus : a molecular and morphological perspective - Edwards, Shelley (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Botany and Zoology))--Unkiversity of Stellenbosch, 2009.